PENGARUH CREDIBILITY ENDORSEMENT DANBRAND EQUITY TERHADAP PURCHASE INTENTION PRODUK GREEN COSMETIC di INDONESIA - D, SHABRINA FEBRIANITA; IRIANTI, LAUDITTA; ARIJANTO, SUGIH (e-Proceeding FTI, 2024)
One of the environmental damages in Indonesia is represented in plastic waste. One source of plastic waste comes from cosmetic products. The use of cosmetics that are environmentally friendly and do not harm the health of consumers is one way to reduce plastic waste. Green cosmetics is a form of cosmetic movement that uses natural ingredients that have a healthy and sustainable concept. However, in Indonesia there are consumer barriers to buying green cosmetic products, namely value barriers, usage barriers, risk barriers, tradition barriers, and image barriers. Therefore, the purpose of this study was to determine the effect of credibility endorsement and brand equity on the purchase intention of green cosmetic products. This research was processed using the Structural Equation Modeling (SEM) method, which is a multivariate analysis technique used to build and test statistical models in the form of causal models with the help of AMOS software. The results of this study show that celebrity cause fit, brand credibility and brand loyalty can influence purchase intention. Abstrak Kerusakan lingkungan di Indonesia salah satunya direpresentasikan pada sampah plastik. Sumber sampah plastik salah satunya berasal dari produk kosmetik. Penggunaan kosmetik yang ramah lingkungan dan tidak membahayakan kesehatan konsumen merupakan salah satu cara mengurangi sampah plastik. Green cosmetic merupakan bentuk pergerakan kosmetik yang menggunakan bahan alami yang mempunyai konsep sehat dan berkelanjutan. Akan tetapi di Indonesia terdapat hambatan-hambatan konsumen untuk membeli produk green cosmetic yaitu value barriers, usage barriers, risk barriers, tradition barriers, dan image barriers. Oleh karena itu tujuan penelitian ini untuk mengetahui pengaruh credibility endorsement dan brand equity terhadap purcase intention produk green cosmetic. Penelitian ini diolah menggunakan metode Structural Equation Modelling (SEM), yang merupakan teknik analisis multivariat yang digunakan untuk membangun dan menguji model statistik dalam bentuk model-model sebab akibat dengan bantuan software AMOS. Hasil penelitian ini menunjukan celebrity cause fit, brand credibility dan brand loyalty dapat mempengaruhi purchase intention.